Engineering β-ketoamine covalent organic frameworks for photocatalytic overall water splitting - Yang, Yan; Chu, Xiaoyu; Zhang, Hong-Yu; Zhang, Rui; Liu, Yu-Han; Zhang, Feng-Ming; Lu, Meng; Yang, Zhao-Di; Lan, Ya-Qian (Nature communications, 2023)
Covalent organic frameworks (COFs) are an emerging type of crystalline and porous photocatalysts for hydrogen evolution, however, the overall water splitting activity of COFs is rarely known. In this work, we firstly realized overall water splitting activity of β -ketoamine COFs by systematically engineering N-sites, architecture, and morphology. By in situ incorporating sub-nanometer platinum (Pt) nanoparticles co-catalyst into the pores of COFs nanosheets, both Pt@TpBpy-NS and Pt@TpBpy-2-NS show visible-light-driven overall water splitting activity, with the optimal H 2 and O 2 evolution activities of 9.9 and 4.8 μmol in 5 h for Pt@TpBpy-NS, respectively, and a maximum solar-to-hydrogen efficiency of 0.23%. The crucial factors affecting the activity including N-sites position, nano morphology, and co-catalyst distribution were systematically explored. Further mechanism investigation reveals the tiny diversity of N sites in COFs that induces great differences in electron transfer as well as reaction potential barriers. Covalent organic frameworks (COFs) are an emerging type of crystalline and porous photocatalysts for hydrogen evolution. Here, the authors report a β-ketoamine COF by systematically engineering N-sites, architecture, and morphology for improved water splitting activity.